Interest Rates in Mexico : The Role of Exchange Rate Expectations and International Creditworthiness - Khor, Hoe (IMF Working Papers; Working Paper, 1991)
This paper explores how interest rates on domestic financial assets in Mexico are linked to expectations of exchange rate changes and to perceptions about the default risks contained in Mexico's external debt. It is shown that the interest rate differentials between peso- and U.S. dollar-denominated domestic assets reflected some concerns about the exchange rate policy during the period under study. In addition, the evidence suggests that the interest rate on a U.S. dollar-denominated Mexican domestic asset is linked (i.e., cointegrated) to the yield implicit in the secondary market price for external debt issued by Mexico.